The effect of applying business intelligence on improvement of information technology management (case study: software companies in Tehran province) - Noruozzadeh, Mohamad Ali (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The purpose of this study was investigating the effect of applying business intelligence in improving information technology management of organization based on data of software companies in Tehran province using data mining techniques in Clementine environment entitled BI-IT.DM. The data is based on a sample of 12,000 data and reports from software companies in Tehran province during the years 2013 to 2018, available in the Organization of Computer Guild of Iran. The initial and proposed model of research was developed after conducting a case study in software companies in Tehran province. The most important results of this study are that the main predictors of the model are predictors of "business intelligence for business IT services strategy with data code (A5)" with predictive weight of 0.34%, predictor "business intelligence for continuous improvement of business IT services with data code (A1) with predictive weight 0.30%, predictor "business intelligence for business IT services transfer with data code (A3). Finally, in order to apply business intelligence to improve the organization’s information technology management, the top companies were categorized into six groups (Class A-F), with optimal ratios of the likelihood of successful use of BI in the organization.